GENEPOOL OF SUBTROPIC, SOUTH FRUIT AND FLOWER-DECORATIVE PLANTS OF THE ADYGH BRANCH OF THE FSBSI ARSRIFSC - B. V. Korzun; E. K. Pchikhachev (Новые технологии)
The article substantiates the need to preserve and replenish the gene pool of subtropical, southern fruit crops and flower-decorative plants in the foothill zone of the North-West Caucasus. In the conditions of the Republic of Adygea such a collection was created for the first time. The complete list of plants studied in the Adygh branch of the FSBSI ARSRIFSC is given, including tea, persimmon, unabi, pawpaw, walnut, hazel, hazelnuts, chestnuts, pecans, apple trees, Kuril tea, flower crops, etc., growing in the collection sites of the Adygh branch of FSBSI ARSRIFSC. The gene pool of fruit is replenished annually: in 2019, the number of unabi variety was increased by five plants, in 2018 walnut-bearing plants were increased due to 1 new variety of hazelnuts «Golovskaya club-shaped» and 1 decorative carmine-red form of hazel. The gene pool of flower and ornamental crops was increased in 2019, including 2 species and 72 varieties.The article describes the subtropical, southern fruit crops and flower-decorative plants from the gene pool of the Adygh branch, which is represented by 159 samples. The results of assessing the state of crops in the conditions of the branch showed that the death of plants due to adverse climatic conditions was not observed. In the foothills of the North-West Caucasus there is great potential for cultivating unconventional fruit and flower-decorative crops from the gene pool of the Adygea branch.